IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN - Sitti Mania (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2010)
The Indonesian society which, in fact, consists of different ethnic groups, religions, languages, and cultures becomes a main reason why multicultural education is of great importance. Multicultural education is originally the study of intercultural and multiculturalism. The nature of multicultural education is democracy, humanism and pluralism which, of course, not in line with authorita-rianism which controls and oppresses human to freedom. The strategy and concept of multicultural education is to make different aspects of students such as ethnic group, culture, language, religion, social status, gender, ability, and age, to be a shared value. This is designed for students to realize the importance of being humane, pluralistic and democratic.